Effects of a synergic interaction between magnesium sulphate and ketamine on the perioperative nociception in dogs undergoing tibial plateau leveling osteotomy: a pilot study - Galosi, Margherita; Pennasilico, Luca; Piccionello, Angela Palumbo; Serino, Federica; Tosi, Francesca; Sassaroli, Sara; Riccio, Valentina; Angorini, Alessio; Salvaggio, Alberto; Di Bella, Caterina (Frontiers in Veterinary Science, 2024)
IntroductionMagnesium Sulphate (MgSO4) is commonly used in human medicine for the management of perioperative pain in different types of procedures. However, in veterinary medicine, the use of MgSO4 has not been evaluated for its analgesic efficacy in dogs, which has generated conflicts of opinion in this area of veterinary anesthesiology. The aim of this study was to evaluate the perioperative analgesic efficacy of MgSO4 in combination with Ketamine in dogs undergoing Tibial Plateau Leveling Osteotomy (TPLO). Our hypothesis is that MgSO4 plus ketamine have a synergistic action in the management of intra-and postoperative pain.MethodsTwenty adult mixed breed dogs with average age 5.9 ± 2.6 years and weight 27.8 ± 9.2 kg were included in this prospective, clinical, randomized study. Dogs were randomly assigned to two groups. The MK group received ketamine (0.5 mg/kg as starting bolus followed by continuous infusion rate at 1 mg/kg/h). At the end of the ketamine bolus, MgSO4 (50 mg/kg over 15 min) was administered by the same route, followed by a constant rate infusion (CRI) at 15 mg/kg/h, IV. K group received a bolus of ketamine followed by a CRI at the same dosage described in MK group. Main cardiorespiratory parameters were recorded 10 min before the start of surgery (BASE), after the ketamine bolus (T1) and the MgSO4 bolus (T2), during the skin incision (SKIN), the osteotomy (OSTEOTOMY) and skin suturing (SUTURE). In the postoperative period, the short form of Glasgow Composite Pain scale (SF-CMPS) was used to assess pain at 30, 60, 120, and 180 min after extubation (Post30, Post60, Post120, and Post180, respectively). The main blood electrolytes (Mg2+, Ca2+, Na+, K+) were analyzed at BASE, T2, OSTEOTOMY, SUTURE and T3 (one hour after stopping MgSO4 infusion). Number of rescue analgesia and administration times were recorded both in the intra-and postoperative period.ResultsIn K group 7 out of 10 dogs required intraoperatory rescue analgesia compared to MK group (3/10). Furthermore, mean arterial pressure (MAP) and heart rate (HR) were significantly higher at OSTEOTOMY compared to BASE time in both groups. In the postoperative period, at T120, ICMPS-SF score was higher in K group than MK group.ConclusionThe administration of MgSO4 could guarantee better analgesia in the perioperative period in dogs undergoing TPLO, performing a synergistic action with ketamine.